The Analysis of Total Solid in Red Yellow Podsolic with age 1-20 years the rearing Catfish (Pangasius hypopthalmus) intensively - Ibnu Hadzqi; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research aims to determ ine the value of total solid in red yellow podsolic soil pond that rearing catfish intensivley with range ages are 1-5, 6-10, 11-15, and 16-20 years. This research using experiment method especially complate random design method. The research was conducted from july to september 2016 in kota masjid village, Kampar district and in laboratorium of aquaculture, faculty of fishiries and marine University of Riau. The highest value of total solid in water surface is in fish pond with range age 6-10 years (12.901,40). The highest value of total solid in floor water is in fish with range age 6-10 years (17.759,66). The highets of fish production pond is in fish range 11-15 yeras (7,46kg/m2). The highest of life extent is in fish pond with range age 15-20 (95,83%) aand the highest of feed conversion is in fish pond with range age 6-10 (2,03). Based on measurement, the relationship of soil quality parameters and water quality parameters is still quite good. Soil quality parameters measured were pH of soil 6,06-6,28 KBOT 1,45-1,84% and BV 1,69-2,46. Water quality parameters measured are temperature 28,71-29,910C,turbidity,29,11-32,29 NTU, pH of water 6,71-6,88, DO 7,35-8.60 mg/L, CO2 18,62-25,51 mg/L, TOM 6,84-7,87 mg/L, alkalinitas 28,91-35,46 mg/L, and hardness 14,43-17,45 mg/L. Keywords: Total solid, Pangasius hypohtalmus, Red Yellow Podsolic, life extent